A Review of the Geothermal Potential Hot Spots in Iraq Using Geophysics Methods - Salloom, Alaa H.; Abdulrazzaq, Omar A.; Sadoon, Sahar; Abdulnaby, Wathiq G. (Journal of Petroleum Research and Studies, 2022)
This review introduces the concept of geothermal energy and the technologies used to harvest this sustainable and clean source. Geothermal systems were explained in details in the review. They were classified into two major types, steam cycle and binary cycle. The steam cycle is always used at higher enthalpy, and a binary cycle is used at low enthalpy. The power generation methods used to produce geothermal power from geothermal resources, typically, comprises of well production, injection and steam and gas separators, heat exchangers, preheaters, turbines and condenser. The steam cycle type allows the water to evaporate and the steam will be separated from brine solution and expanded in a turbine, generally the salty water will have discarded out of system, or it is flashed again at lower system part. Power generation methods were divided into single Flash Steam Plant, Double Flash Steam Plant, and Dry Steam Plant. The components of the geothermal power plant were elucidated, namely, feed pump, heat exchanger, preheater, evaporator, turbine, and condenser. After surveying the geothermal energy worldwide briefly, the Iraqi geothermal energy was introduced. Thermal gradient in Iraqi tectonic zone was analyzed. There is a very limited available literature on Iraq geothermal. However, we were able to analyze the geothermal temperature gradient in Iraq by dividing it into two regions; the northern Iraq, and the southern Iraq. Our analysis shows that Iraq is a poor zone for geothermal with no significant hot spots all over the country. However, low temperature applications can be invested using the exhausted petroleum wells.